Eksplarasi Cara Guru Matematika SMP Mengajar Selama Covid 19 - Lutfilah, Helmi; Purwanto, Sigid Edy (International Journal of Progressive Mathematics Education, 2023)
The purpose of this study was to find out how to explore the way junior high school mathematics teachers taught during Covid 19. This research was carried out in schools in the Tanah Abang District, Central Jakarta in the even semester of the 2020-2021 school year. The research method used was a qualitative approach with this type of research. case study (case study). Data collection techniques by observation, interviews and documentation. The research subjects were junior high school teachers who taught in Tanah Abang District, Central Jakarta, consisting of 7 math teachers, 4 male teachers and 3 female teachers. This study used technical triangulation, namely checking data using different techniques to match exploratory data on how junior high school teachers taught mathematics during Covid 19 with observation, interview and documentation techniques. The results of the study show that learning during the Covid 19 era brought significant changes in the way junior high school mathematics teachers taught, which was shown in several aspects studied.